Early results from the use of an innovative vertical fascial traction system for the management of patients with open abdomen - Ioannidis, Orestis; Brenta, Aliki; Theodorou, Alexis; Siozos, Konstantinos; Gemousakakis, Georgios; Anestiadou, Εlissavet; Klonou, Ekaterini; Symeonidis, Savvas Konstantinos; Bitsianis, Stefanos; Kotidis, Efstathios; Mantzoros, Ioannis; Pramateftakis, Manousos Georgios; et al. (Frontiers in Surgery, 2025)
BackgroundThe combination of negative pressure wound therapy (NPWT) with dynamic fascial traction is currently considered the preferred method for temporary closure of the open abdomen (OA). However, this approach often requires repeated returns to the operating room for further fascial approximation. The aim of this study was to present our institution's experience with a vertical fascial traction device (VTD) for OA management and early closure.MethodsThis is a prospective registry of patients treated with the VTD between May 2023 and the present. The system used is commercially named Fasciotens® Abdomen, manufactured by Fasciotens GmbH (Essen, Germany).ResultsDefinitive abdominal closure was achieved in 11 of 13 patients. Eight patients underwent primary midline suture, while 3 patients—all with pre-existing hernias—required mesh reinforcement. Two patients died before closure could be performed.ConclusionsThe vertical fascial traction device applies continuous upward traction to the rectus abdominis fascia through an external frame anchored to the pelvis and thorax, thereby increasing abdominal compartment volume and reducing intra-abdominal pressure. This innovative technique facilitates earlier and safer abdominal wall closure and represents a promising adjunct in the management of the open abdomen.